A taxonomic contribution to yellow-flowered members of Centaurea sect. Phaeopappus (Asteraceae) in Iran - Ranjbar, Massoud; Heydari, Razayeh (Phytotaxa, 2016)
Centaurea salmasensis and C. zagrosmontana, two new species endemic to Iran, are described and illustrated. These new species belong to C. sect. Phaeopappus. Centaurea phaeopappa subsp. jiroftensis is raised in rank as C. jiroftensis. A key to yellow-flowered species of the section in Iran is provided.